Research methodology - Murthy C (New Delhi Vrinda Publictions, 2019)
Research in branches of social sciences; decisional research; business research; types of research and approaches; review of literature; role of computers in research; research design; testing of hypothesis; sampling and sampling design; methods of collection of data.
Keywords: Research Methodology